Intelligent Home: Automated, Secured & Medically Monitored - Hafeez, Farrukh; Hamid, Muhammad; Azhar, Ameer (Journal of Telecommunication, Electronic and Computer Engineering (JTEC), 2017)
This research focuses on Intelligent Home with security system, indoor and outdoor automation system and medical monitoring system with a mobile alert for retarded and impaired person. It presents the use of Android application to implement home security using RFID, dealing with outside home automation system using automated irrigation system techniques, inside home automation using smart sensors and medical remote monitoring system using implanted RFID tag. Voice commands and voice feedback and acknowledgment are also parts of the proposed system.